Pharmacological Inhibition of WEE1 Potentiates the Antitumoral Effect of the dl922-947 Oncolytic Virus in Malignant Mesothelioma Cell Lines - Iannuzzi, Carmelina Antonella (Int J Mol Sci, 2020)
Malignant mesothelioma (MM) is a very aggressive asbestos-related cancer, for which no therapy proves to be effective. We have recently shown that the oncolytic adenovirus dl922-947 had antitumor effects in MM cell lines and murine xenografts. Previous studies demonstrated that dl922-947-induced host cell cycle checkpoint deregulation and consequent DNA lesions associated with the virus efficacy. However, the cellular DNA damage response (DDR) can counteract this virus action. Therefore, we assessed whether AZD1775, an inhibitor of the G2/M DNA damage checkpoint kinase WEE1, could enhance MM cell sensitivity to dl922-947. Through cell viability assays, we found that AZD1775 synergized with dl922-947 selectively in MM cell lines and increased dl922-947-induced cell death, which showed hallmarks of apoptosis (annexinV-positivity, caspase-dependency, BCL-XL decrease, chromatin condensation). Predictably, dl922-947 and/or AZD1775 activated the DDR, as indicated by increased levels of three main DDR players: phosphorylated histone H2AX (γ-H2AX), phospho-replication protein A (RPA)32, phospho-checkpoint kinase 1 (CHK1). Dl922-947 also increased inactive Tyr-15-phosphorylated cyclin-dependent kinase 1 (CDK1), a key WEE1 substrate, which is indicative of G2/M checkpoint activation. This increase in phospho-CDK1 was effectively suppressed by AZD1775, thus suggesting that this compound could, indeed, abrogate the dl922-947-induced DNA damage checkpoint in MM cells. Overall, our data suggest that the dl922-947-AZD1775 combination could be a feasible strategy against MM.